Un avenir post-nucléaire ? Les atermoiements des acteurs du territoire de Trino (Italie) en contexte de démantèlement - Maude Gallimard; Cesare Mattina (VertigO)
Although nuclear power generation has stopped in 1990 and the decision has been taken to accelerate the process towards an "immediate dismantling" of the Enrico Fermi plant, the people of Trino (Po plain, Piedmont) find it difficult to imagine and plan a post-nuclear territory. This contribution tries to explain why the post-nuclear phase is not so obvious and the reasons that are largely holding it back. From a diachronic perspective, this article shows how the various actors and social groups of this territory went through the phase of decline in nuclear production (referendum of 1987 decreeing a moratorium on the construction of new plants), the uncertain phase of the shutdown of nuclear power plants production (1990), and then passive safety (1990-2003) and dismantling (since 2003) to settle in the lasting uncertainty of dismantling and waste management, waiting for a national repository that, in Italy, has still not been realized. Despite projects and initiatives to imagine and build post-nuclear territories through the development of green and quality tourism or renewable energies, most of the actors involved at the local scale remain in rhetoric and actions tending to confirm the continuity and legitimacy of nuclear power on its territory, sometimes against their own beliefs. In view of the demographic decline and the process of the deindustrialization of its territory, nuclear power, with, on the one hand, jobs in dismantling and, on the other hand, the state compensation funds paid to municipalities for the hosting of radioactive waste, remains an essential sector of this territory.